Development of Pop-Up Book Learning Media on IPAS Class IV Elementary School Energy Material - Gadis Dwi Mafithroh; Desi Wulandari (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop and test the feasibility, practicality, and effectiveness of pop-up book material on changing the form of energy. This research is a research and development that refers to the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). Data collection techniques used test techniques (pretest-posttest) and non-tests in the form of observation, questionnaires, interview results, and document data. The results of validation by material and media expert validators showed that the pop-up book met the valid criteria with an average score of 91.4%. Based on the results of the pretest-posttest, the results show that pop-up books are effective in improving student learning outcomes with the results of an increase in the average pretest score of 50.68 to 84.77 on the posttest, the N-Gain test results obtained were 0.73 with a high category. Based on the results of the response questionnaire, a positive response was obtained from teachers and students. From these results it can be concluded that the pop-up book on the material of changing the form of energy is effective for improving student learning outcomes and is feasible and practical to use in learning IPAS grade IV SDN Ngijo 01 Semarang City.